2017
DOI: 10.1515/jpem-2016-0356
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tanner staging of HIV-infected and uninfected girls at the University of Nigeria Teaching Hospital, Ituku/Ozalla, Enugu, Nigeria

Abstract: Perinatal HIV infection affected the onset of pubic hair and breast development but did not significantly affect the attainment of sexual maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
7
8
2
Order By: Relevance
“…9,10,93 Whereas 70% of HIV-infected girls in the index study had attained puberty, Mbwile, [22] reported lower proportions in Tanzania where only 49% of HIV-infected females were found to have attained puberty. The proportion of HIV-infected females who had attained puberty in this study was also higher that reported by Iloh et al, [23]…”
Section: Discussionsupporting
confidence: 51%
“…9,10,93 Whereas 70% of HIV-infected girls in the index study had attained puberty, Mbwile, [22] reported lower proportions in Tanzania where only 49% of HIV-infected females were found to have attained puberty. The proportion of HIV-infected females who had attained puberty in this study was also higher that reported by Iloh et al, [23]…”
Section: Discussionsupporting
confidence: 51%
“…Among PHIV youth in the US, delays in pubertal onset were observed for those with lower CD4 counts or higher viral load as compared to healthier PHIV youth [30]. In a small cross-sectional study conducted in Nigeria, a significantly lower percentage of HIV-infected girls had pubertal onset than an age-matched group of uninfected girls [32]. In longitudinal follow-up of HIV-infected ARROW trial participants in Africa, the observed mean ages at pubertal onset were 12.8 for boys and 11.7 for girls; the estimated mean age at menarche was 14.3 years [31].…”
Section: Pubertal Development In Hiv-infected Adolescentsmentioning
confidence: 99%
“…The physical growth and sexual maturation of perinatally-HIV infected male and female children have been well documented in studies conducted in developed and developing countries. In Nigeria, the few published studies that evaluated these outcomes were conducted in perinatally HIV-infected girls alone [ 20 , 23 ]. Thus, it is important to obtain data on similar outcomes among adolescent males seen in this clime.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas studies demonstrating growth and pubertal delay in male and female HIV-infected children have been conducted in the developed settings of Europe and the United States [14][15][16][17], similar studies in either of the sexes or both sexes have been conducted in sub-Saharan Africa as well [18][19][20][21][22]. In southeast Nigeria, a previous study in this locality focused on the female sex alone by investigating sexual maturation in perinatally HIVinfected girls aged 8-17 years [23]. The present study, however, aimed to determine the physical growth and sexual maturation of perinatally HIV-infected adolescent males and compare them with those of age-matched HIV-negative controls.…”
Section: Introductionmentioning
confidence: 99%